The Effect of Pellets and Natural Feed Combination in the Form of Insects on the Protein Content of Catfish (Clarias sp.) in the Minapadi Cultivation System - Trinandita, Syfa; Aminatun, Tien; Suhartini; Putri, Rizka Apriani; Budiwati; Sujangka, Arsyad (Jurnal Sains Dasar, 2025)
This study aims to analyze the effect of the combination of pellets and natural feed on catfish protein levels in the minapadi system. The method used was an experimental design with two feeding treatments, which were treatment A (a combination of pellets and natural feed) and treatment B (pellets only). The natural feed consisted of insects available within the minapadi system, while the pellets used were commercial pellets. The study was conducted for 76 days in the rice field area of Donotirto Village, Kapanewon Kretek, Bantul Regency, Special Region of Yogyakarta. Catfish protein content was tested using the Kjeldahl method. The data obtained was statistically analysed using an independent t-test. The average protein content of catfish in treatment A was 16.17%, whereas that in treatment B was 16.89%. The statistical analysis indicated that the combination of pellets and natural feed had no significant effect on the protein content of catfish. These results are presumably influenced by the limited availability of insects during the study, which limited their contribution as natural feed to significantly enhance the protein content of catfish. Theese finding indicates that the utilization of insects within the minapadi system requires improved management and adjustments in cultivation practices to increase their availability. Further studies are therefore necessary to explore alternative natural feed sources as well as modifications to the minapadi system that could enhance insect availability as an additional nutritional resource for catfish.